Three-dimensional CRISPR screening reveals epigenetic interaction with anti-angiogenic therapy - He, Michael Y.; Halford, Michael M.; Liu, Ruofei; Roy, James P.; Grant, Zoe L.; Coultas, Leigh; Thio, Niko; Gilan, Omer; Chan, Yih-Chih; Dawson, Mark A.; Achen, Marc G.; Stacker, Steven A. (Communications biology, 2021)
Angiogenesis underlies development, physiology and pathogenesis of cancer, eye and cardiovascular diseases. Inhibiting aberrant angiogenesis using anti-angiogenic therapy (AAT) has been successful in the clinical treatment of cancer and eye diseases. However, resistance to AAT inevitably occurs and its molecular basis remains poorly understood. Here, we uncover molecular modifiers of the blood endothelial cell (EC) response to a widely used AAT bevacizumab by performing a pooled genetic screen using three-dimensional microcarrier-based cell culture and CRISPR–Cas9. Functional inhibition of the epigenetic reader BET family of proteins BRD2/3/4 shows unexpected mitigating effects on EC survival and/or proliferation upon VEGFA blockade. Moreover, transcriptomic and pathway analyses reveal an interaction between epigenetic regulation and anti-angiogenesis, which may affect chromosomal structure and activity in ECs via the cell cycle regulator CDC25B phosphatase. Collectively, our findings provide insight into epigenetic regulation of the EC response to VEGFA blockade and may facilitate development of quality biomarkers and strategies for overcoming resistance to AAT. Through three-dimensional CRISPR screening, He et al. report that functional inhibition of BET family of proteins BRD2/3/4 shows mitigating effects on blood endothelial cell (EC) survival and/or proliferation upon VEGFA blockade. An interaction between epigenetic regulation and anti-angiogenesis, which may affect chromosomal structure and activity in ECs through CDC25B phosphatase, is potentially involved with EC resistance to anti-angiogenic therapy.